PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 - Monika Tamaka; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2023)
Company value is the performance of a company which is reflected by the share price which is formed by the demand and supply of the capital market which reflects the public's assessment of the company's performance. Factors that have a very large influence on company value include company size, liquidity and profitability This study aims to determine the effect of company size, liquidity, and profitability on firm value in banking sector companies listed on the IDX in 2018-2021. The research was conducted using the non-participant observation method, the data used was in the form of secondary data obtained on the Indonesia Stock Exchange (IDX) through the website www.idx.co.id. The samples used in this study were 14 companies which were determined using purposive sampling method. The analysis technique used in this research is Multiple Linear Regression The results of the study show that firm size has a positive and significant effect, liquidity has a non-significant negative effect, and profitability has a negative and significant effect on firm value.